TI_GERICHTE 14.2011.198 vom 14. Dezember 2011 , Reclamo contro la dichiarazione di fallimento. Solvibilitâ non resa verosimile - TI Tribunale d'appello (2011)
Reclamo contro la dichiarazione di fallimento. Solvibilitâ non resa verosimile